[Gly²]-GLP-2, But Not Glucagon or [D-Ala²]-GLP-1, Controls Collagen Crosslinking in Murine Osteoblast Cultures - Mieczkowska, Aleksandra; Bouvard, Beatrice; Legrand, Erick; Mabilleau, Guillaume (Frontiers in Endocrinology, 2021)
Bone tissue is organized at the molecular level to resist fracture with the minimum of bone material. This implies that several modifications of the extracellular matrix, including enzymatic collagen crosslinking, take place. We previously highlighted the role of several gut hormones in enhancing collagen maturity and bone strength. The present study investigated the effect of proglucagon-derived peptides on osteoblast-mediated collagen post-processing. Briefly, MC3T3-E1 murine osteoblasts were cultured in presence of glucagon (GCG), [D-Ala²]-glucagon-like peptide-1 ([D-Ala²]-GLP-1) and [Gly²]-glucagon-like peptide-2 ([Gly²]-GLP-2). Gut hormone receptors expression at the mRNA and protein levels were investigated by qPCR and western blot. Extent of collagen postprocessing was examined by Fourier transform infrared microspectroscopy. GCG and GLP-1 receptors were not evidenced in osteoblast cells at the mRNA and protein levels. However, it is not clear whether the known GLP-2 receptor is expressed. Nevertheless, administration of [Gly²]-GLP-2, but not GCG or [D-Ala²]-GLP-1, led to a dose dependent increase in collagen maturity and an acceleration of collagen post-processing. This mechanism was dependent on adenylyl cyclase activation. In conclusion, the present study highlighted a direct effect of [Gly²]-GLP-2 to enhance collagen post-processing and crosslinking maturation in murine osteoblast cultures. Whether this effect is translatable to human osteoblasts remains to be elucidated.